An analysis of the benefits, challenges and methods of process selection to adopt robotic process automation - Grande, Vinicius Augusto; Campos, Renato de; Facin, Ana Lúcia Figueredo; Batistela, Gislaine Cristina (Revista Gestão da Produção Operações e Sistemas, 2022)
Purpose - Robotic Process Automation (RPA) is an emerging business tool that has gained the attention of organizations aiming to improve and transform their processes. However, RPA is not a solution that fits all existing scenarios and thus carefully-considered analysis is required before its implementation. This study aimed to carry out an analysis of the benefits, challenges and methods of selecting the most appropriate processes to be prioritized in RPA implementation projects. Theoretical framework - In addition to the basic concepts, the article was based on research in the literature that specifically deals with characteristics and methods for selecting processes to be automated with RPA. Design/methodology/approach - This is an applied, qualitative and exploratory research study that has adopted the literature review method to identify characteristics related to RPA technology. Articles were searched for from three academic sources: Science Direct, Scopus, and Web of Science. Findings - In addition to cost savings, the benefits identified were accuracy, productivity, and consistency. Benefits obtained in several areas of the industry were also synthesized. As challenges, common mistakes in projects where automation implementation failed and problems multiplied, such as a lack of training and support, were identified and listed. Finally, methods considering different characteristics and criteria were described in order to define organizational processes most compatible with RPA. Research, Practical & Social implications - Thus, the study seeks to contribute to the decision-making of those wishing to understand and introduce this technology into their organizations, enabling them to appropriately select processes to be automated with RPA. Originality/value - Despite the rapid development of the market in relation to process automation, no single model or guide for the proper selection of processes to be automated with RPA was identified, and each method found in the literature has specific characteristics. Keywords - RPA; Robotic Process Automation; Benefits; Challenges; Methods.